ANALYSING LOGISTIC MANAGEMENT OF CULINARY SMALL AND MEDIUM ENTERPRISE IN THE COASTAL AREA IN MANADO (STUDY CASE OF DABU-DABU LEMONG RESTAURANT) - Kerap, Stephenny K. R.; Pangemanan, Sifrid S (Journal of Asean Studies on Maritime Issues, 2017)
Small and Medium Enterprises have significant roles in developing the economy. Therefore developing SMEs is crucial to do including empowering the core business process of SMEs especially in culinary sector. The culinary sector is important because it might help to promote Manado through the food they provide. The culinary SMEs that lately became famous in Manado are the grilled fish restaurants especially those located in the coastal area of Manado that have high potential in attracting consumers due to their restaurantâ€™s location that built in the coast area which also help to add business competitiveness. In culinary SMEs, providing the food is the most critical aspect to do. Logistic management became crucial as a business activity that supports the Production and Operation Management. Logistic Management key activities considered as the indicators in determining the current logistic management performance and strategies applied by Dabu-Dabu Lemong restaurant to reach the satisfying level of logistic management performance. Using Qualitative research methodology, the owner of Dabu-Dabu Lemong restaurant was being interviewed and the result showed the logistic management performance of Dabu-DabuÂ  Lemong culinary SME in Manado is in proper condition and there are total of 8 logistic management strategies that generated from this research.Keywords: Logistic Management, Small and Medium Enterprises